1998
DOI: 10.1159/000009925
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Thermal Coagulation – Degree of Uterine Fibrosis Predicts Treatment Outcome

Abstract: Objective: To study the uterine cavity after thermal endometrial destruction for the treatment of menorrhagia by means of a balloon catheter, the CavatermTM system. To relate the appearance of the uterine cavity to the outcome of the treatment. Methods: Fifty-one of the first 60 women treated with balloon endometrial destruction were examined with hysteroscopy and saline infusion sonography 11–28 months after treatment. Results: Patients with minimal or no bleeding after thermal endometrial destruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…In a study performed by Friberg et al [2], all patients had an endometrial thickness !5 mm 11-28 months after thermal endometrial destruction. In our patients, 27% of them had a double-layer endometrial thickness 15 mm which suggests that thinning of the endometrium might proceed even after 6 months have passed since the procedure.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In a study performed by Friberg et al [2], all patients had an endometrial thickness !5 mm 11-28 months after thermal endometrial destruction. In our patients, 27% of them had a double-layer endometrial thickness 15 mm which suggests that thinning of the endometrium might proceed even after 6 months have passed since the procedure.…”
Section: Discussionmentioning
confidence: 97%
“…When hysterectomy has been performed immediately after thermal balloon endometrial ablation therapy, the mean thickness of the coagulation zone has been found to be between 3.5 mm [7] and 7.6 mm [4] on light microscopy and 4-5 mm on electron microscopy [7]. Several months after thermal balloon therapy, the hysteroscopic view resembles contraction of the uterine cavity subsequent to fibrosis [2,6]. We have reported earlier [10] that thermal balloon endometrial ablation therapy induces a rise in uterine blood flow impedance, but not until 6 months after the treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increased impedance is due to decreased blood flow during diastole, because ED and TAMX were decreased, whereas PS remained unchanged. Friberge & colleagues, concluded that; the greater the fibrosis of uterine cavity after ablation was associated with better prognosis [25]. Twenty-seven (27) women with either menorrhagia or endometrial hyperplasia without atypia, were randomized to receive either thermal balloon endometrial ablation therapy or medroxyprogesterone acetate by Dr I. Järvelä and colleagues [26].…”
Section: Discussionmentioning
confidence: 99%